Stockpiling of Cdc25 during a DNA replication checkpoint arrest in Schizosaccharomyces pombe. - Kovelman, R (1996)
The DNA replication checkpoint couples the onset of mitosis with the completion of S phase. It is clear that in the fission yeast Schizosaccharomyces pombe, operation of this checkpoint requires maintenance of the inhibitory tyrosyl phosphorylation of Cdc2. Cdc25 phosphatase induces mitosis by dephosphorylating tyrosine 15 of Cdc2. In this report, Cdc25 is shown to accumulate to a very high level in cells arrested in S. This shows that mechanisms which modulate the abundance of Cdc25 are unconnected to the DNA replication checkpoint. Using a Cdc2/cyclin B activation assay, we found that Cdc25 activity increased approximately 10-fold during transit through M phase. Cdc25 was activated by phosphorylations that were dependent on Cdc2 activity in vivo. Cdc25 activation was suppressed in cells arrested in G1 and S. However, Cdc25 was more highly modified and appeared to be somewhat more active in S than in G1. This finding might be connected to the fact that progression from G1 to S increases the likelihood that constitutive Cdc25 overproduction will cause inappropriate mitosis.